Quality FDI and Supply-Chains in Manufacturing: Overcoming Obstacles and Supporting Development - Theodore H. Moran; Holger Görg; Adnan Seric (Kiel Centre for Globalization (KCG), 2016)
This paper aims to identify the obstacles to attracting "quality" foreign direct investment (FDI) in middle-skill manufacturing activities, so as to inform an action-agenda for policies that will help developing and emerging market economies to link into global supply chains while building backward linkages deep into their own economies. The evidence reviewed here shows positive benefits from external advice and support in creating supplier data-bases, setting up qualification and certification programs, training talent scouts and brokers, and forming financing programs backed by purchase agreements from foreign buyers. Thus, in the contemporary era in which trade and investment are increasingly intimately linked, support for developing and emerging market economies to use quality FDI to upgrade and diversify their production and export bases – and to develop reliable and competitive supply chains deep into the local economy – is the new frontier for assistance from the developed countries and multilateral community looking to the future.
Keywords: 330